A Compositional Approach to a First Dynasty Inscribed Label Fragment from the Abydos Tomb Complex Ascribed to Qa′a - Piquette, Kathryn E. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
The case study presented in this article takes a compositional approach to the reconstruction of an ivory label fragment (Ashmolean E.1262) discovered over a century ago by Flinders Petrie and his team at the Abydos tomb complex ascribed to Qa’a, the last ruler of the First Dynasty. Previous methods applied to the study of labels and other early inscribed objects and the modes used for their reproduction in printed media are discussed and critically assessed. I argue that the pitfalls presented by anachronistic and de-contextualising approaches can be avoided by anchoring analysis in the artefact in tandem with detailed comparative study of contemporary graphical culture. Previous reproductions and reconstructions are thus reviewed and an adjusted reconstruction of the label fragment is proposed from this grounded perspective.